Tangent and Normal-Derivative PP1

Download as pdf or txt
Download as pdf or txt
You are on page 1of 46

Tangents s

Normal
Past Paper
Problem s
1)

-> cas (i) h = 3

(ii)K = 2

(b) :: flse)=- (a-4)7+K


↓ flaS=-(2-35 + 2
↓ fel) = -
(0-50 + 9) + 2
fURS
↓ = - 05+60-9 +2

f()
·
= - 2 + 62-7
f)
->
= -
2+ 60-7

if CH3 = -
24 + G

(i): f()
->
=- 24+ 6

·
.
slope of the tangent at 4 m=-2(4) + 6

M=
=> -8 +6 =-2

Line 1
through G is
perpendicular to the
·

tangent at @ = M1 x Mc = -1

Me=
=>
= =
= E
iiisy-ge = M(x-cle) = (9,2) 9 m =
E
1
Y-1= = (2-44

:Y =
En-2+1
:Y =
Ex-1
intersect
-> ->
solving simultaneously

↳-Y =
Ex-19
curve -> fla) = 0+0 -
7

:.
Ex-1=-1+02-7
:Ex=-1+6x-7+1
=-4"+ox-G
↓Ex
↓ 1 = = 20+120-12

: 24"-114+12 = 0 2
-
4
M
ed"-8x-34 +12 =0
-
8-3

↓ ex
92-4)-3(0-4] = 0

[x-4] [22-33

= 0

1 1-4=0 120-3 = c

:x = 4 (c =
= Ex-coordinate of
Ris 2 or 1.5
2]

(i)p=-209
->
= G

(ii) y = a (c+2) (0-4)--1)

(6,8) = 8 = a (6+2) (6-4)


(sles =
fle) ==
5
=> a
=
=
2

Citisg==(x+2)(2-4) =
(-4x+ex-s)
·
T=Epi-ex-=Ext-x-a
(i):
->

Y =
Enkx-4

↓= = (ea) -
1-0=x-1

(ii) Gradient of the Tangent at 4 is 7

: M = 7 = 7 = 4-1

=x = 8

=>
D =
E 185-18)-6=9-12
y=32-12 20
=>
=

=P =
18,20)

-> m at $14,0) = M1 [1-1 = 4-1 = 3

Gradient of L
perpendiculate to the tangent at B

I
Me =
-

- |

Eq. of 1 =
y-0=-f(x-a)
=>

y=-fe+g
=>
-> Intersect ->
solving simultaneously
↳ -Y =
-E1 += ta
curve ->
y =
x-x-4
:.
(h) =
Ecrx-4=x8

2 (-2 + 4) = 3(0-24-8)
↓ .
-
20+8 = 34-62-24

O = 34-04-24+ 24-8


O = 30-42-32

?
a=
9() FEC

:x =- =
4 I 20

:4 =
40 Is =
18
:x
= Is = -E
G

↓R = 4
I & 8
--
B
37

-> (as flee)=30-5x+K


-> f (n) = 3 (n) -
5(1) + 0

->
f(d) = 60 -
5

(b) The equation of the


tangent at 42p is

Y = 72-9 = M = 7

F
1
= 60-5 = 60 = 12 + 1= 2

p= 2
=>

(c) Substitute 4 = 2 in flasz344-34+K


(e)
- =
3(2)= 5(2) + K

+12) = 12-10+ K

f2) =+ K 2

Also oY = 701-9 = y = 7(23-9 = 14-9 = 5

y(e) = f2S 2 5 = 2+K=K = 3


u

ca) is
flee)=-x+el + 4 = f)
=- (ea) + (1) + O
->

f')
=>

=-3e + 1
iii) when
ezc=M=-(+1=-3+1 =-2

·Y-Yz=-(2-4e)
Mt

:Y-3=-t 1-2) => y-3 =


E(-2)
Y
=> =
Ex-1
Y=Exte
=>

(iii) 2+x+4
=x +2
=-

Cant1s)
S #4(44) = 27-34+4u+1

4e+S
=>
= -S4F+84 +32
30-0x+44-8 = 0 -24
6f4
Se-44-16
-

=>
= 0
3e Cd-2) + 4(2-2) = 0
30-24-8
=>
= 0

10 -2) (32+4) = 0

(x-2) 332+4)
=> = 0

I
30 + 4 0
M-2 = 8
=
=>

M
=
=2
2 = -

G

-
(are)

-> f(es) = 4-3-eax+1


f(e) = 34-02-24
·
.
Tangents are
parallel to x-axis m = f'(2) = 0

:. 34-60-24=0

↳ 2-ex-8= 0

- 2 -44+ 20-8 = 0

↓ sd-43 + 2 (0-4) =0


D-43 (9 +2) = 0

↓ x-4 = 0 /4+2 = 0

↓ a = 4 12 = - 2

when x= 4 => y (9)


=
- 3(45-24(4) +1

=>
y = 64-48-96+1 =-79 & (4,79)
when 4 =
= 2
=y = 125-37-25-24(-2) +1

=> y =-8-12 +48 +1 =29 I PC-2,29)


N1 Mz

16,293

·d.
i t
-

(i) (4, 29)


(ii) (-2. 79)
-
6

-
CaM)

-
(2193
->
(a) flc) =3000(2n) + sin()

↓ flees = 3c0s(2n3 + [sin(us]"


·
fix) =
35-sincensl ·AIIn) + 2[sixcus]FdIsinxi
↓ fice) =
35-sin(ens]. (2) + 2 sinc).cas (n)

: f(es) =
-
6 six less + six(es)

↓ f() = - 5 sin (22)

(b) Equation of the normal to the curve is x-K


M

Tangent is exactly Horizontal T

:.
Slope of the
Tangent = 0

! f (x) = 0

-
-
Ssin (22) = 0

= sin (en) = 0

ex=

sin*(0) =
0,5, 25

1 x =
8. E, = 0, E, T 1::Ian* =4e
7)

->
ca)
↳is p== g

5
2 =

(ii) Axis of symmetry


#S==3
=

I 2= 3

->
y = (2-1) (x-4) 4 x = h = 3

·
K = (3-1) (3-4)= (2) (-1) = - 2

:
Y = (2-3)-2

->

s =2x-3)
d(a-s)-0 =2(4-3) (2-0) =2(n>

M. at 10.5)
->
= M+ = 2 (0-3) = -
S

y-5
·
= =
6/4-0) -y-5=-64 = y -
= 60+ 5
8T

-> when 1111 y = 4 (13+2(1) = 4+2 = G

·
fS = 42"+ Ex

f (d)

= 4 (524 + 2 (IS

↓ f (= 1284 + 2

:.
M+ = 12(15+2
: .
MT = 14

Eq. of Normal
-y-Y2=ca-es
·

(1, 8) =>
y-0=-f -| (n -
-)
af

cas
->
f(x) = = Cas (e)
224 u
e9%.d(es)
24
4 =
=>
= = 20

↓ = costs xE - six (e)

- () -
= 24 six (n) + 2e"c0s()

: fics) = =* (ecosca)-six (s]

(b) when x=0 = y = esc) = (1S11) = 2

& when 4= 0 -> m = f '10) = e' (ecosco)-sin(0]

M5 1[2(1)-07 2
=>
=

=> Equation of Normal


-Y-1== (0-0)

I y =
-Ex +1
10T

9
-> 4= e4 = = e

↑= cos(e) X=
- six (n)

f)
=>
= (24) (-sin (n)) + (e2) (c0s(n))
"
f)
=> = =
[cos)-sin(as]
At
=> 0 = = = f (t) =
M+ =
(c034)-sinCat]
=
-
I

M+
=>
= 0 41-1-0] =-e

gradient of hornsal =Mn=


=
I -
-
e
- T
= Mm =
Ez or &
11]

2
-> (a) flue) = 0 = (2)

f'(m) (n)#2
= ef
=>
=

ca.2)
ha==t =
* M=
+ =

Equation of Normal is

1 -

31 =- 1 (x-41)
Mt
=> y-e=
=a)(eva)
=y-2 = -

4(2-9)

Y
=>
= -
44+16 +2

y
=>
=-44+18

(b) 2-
intercept: y = 0

= 0 =
-
42 + 18

= 42 = 18

=> x =
18=1
12]

A(1.3)
->
lies on the curve - fle) =
prt+qc
3
=> =
p(157+9(1)
p+9=3-1)
=>

the
tangent at A (1,3) has gradient 8

=>

flse) =
pr+qp
f()
=> =
p122) + 9(1)

=>
8=<p(1) + 9

ep +9
=>
= 8-(2)

From (1)=p=3-91 <p+9 = 8

=> 2(3-4) + 9Eg

6-29 +9
=>
= 8

= 6-9 = 8

2
d=
= =

p-3-c-2)
=>

= p = 5
13]

-> At P11KS = f) =
1(423)
f C1)
=>
= 1 (4 (19%)

f (IS=
=>
M= = 4K

Mm
= F
=>
=

Normal is parallel to
y=-Ex
=>
=
9K

=-8 = -4K

2
=>
= K
14]
->

(i) fee) = a
3

3
·
f (d) = a

P
=>
Da, a3)

⑨1, 0)
Mpa=ear
=>

=m
=
m
=>

=
(ii) f(x) = 23

=> f ) = 322

=> f'(d) = 394

Citis f'ca) = m => sa


=
sa"(a-1) a
=> =

a
=>
--= -

a
=> -

= =
1 =
2 =
= = a = 1
15T

-> cas when a = 1 y


=> = f 1) = 2925 = 2

fa) 20 = +3 2(22) 40
·
= = =


Mi = 4(1324 at 0= 1

Y-2=4(4-1) = y = 44-4+2 EY = 44-I

(b) 21-intercept:y = 0 = 0 = 42-2

Gd = 2
=>

a
=>
=
= =
E
10]

f(x)
-> =
CF+2
: f) =
(2n) + 0 =
2
=
We
At (9.6) = MT =
3 = 2


Y-6 = 2 (0-4)

"Y = ex- Of G

20-2
!Y =
17]

-> (a) f(x) = e*" = f') = 25". (0) = be04

(b) (i) At P(0,b) = M+ = 6.84=6e= 111) = 0

(ii) P(0,b) lies on the curve => flu) =-64


b=
=>
2010se8=1
(c) Tangent: y-= Mr (21-411)

y-1
=>
6
=
(2-0)

y
=>
= Gx +1
18]

tis)
(a) (i)
==
->

cii, b=
piod= = E
=>
=
D

16) fen) = f'(2) =0 EP is minimum pointly


(a) Equation of Normal 1x = 2
19]

-> (a) f(2)= ar -one = fMn) = a (327 - 6 (2n)

f(= 3,94-224
=>

(b) m = 3 when at Pix = 1


3=39 (1)"-12(1)
:3+12 =39

↓ 3a = 1S


a= 5
20]

flae) = sin(e)
+Ez-ex
->

:f (n) = (034)
+E (R2) -2(2)
↓ f (= c0s(e) + 21 -
2

(b) 9 (4)
g10) 5 5
-> = 29 = 2 =

sox14,5)
*

i
(0,53

(2, x)

(c)-> (is glze) = 9 (a-n)+3


H= 2

(ii)g(0) = 5 = 5 = a (0-258+3
a
=>
= a (4) + a =
E =
=
to f
->
Tangent is Parallel to
Tangent to
g
f'cm)
=>
=
g)
COs (2) +11-2
=>
-
9Ex-2)+3}
castes
=> + se = =
E.gecestfl-x+o
cose)
=> +e 2 =

E541-2). 11-013
-

crs()
=>
+H-2 = (0-2)
cas(S
=>
= 4-2- 41+2

cos(e)
=>
= O

c05CO)
e 1, Ea
=>
= =

O(n <a
=>

= x =
&
21

14%
-> f(x) = = f n=
f 12n) = 94.12)
0

f)
=>
= 2224

At lies = M+ = 29214-202
y-91= M+ (2-41)
=>

y-e=
=>
20" (4-1)
=>
Y = 29-2e"+e?

y
=>
= 2e-e?
22]

42
->
(a) flee) = Ws= (44+ 3)

i
f)=E(bx+554. A lan+s)
fica)=s1412) to
·

fid)=etts Fts
·

:11)
Ws Fa
=

if (1) =
=

For
->

glas): Equation of Tangent is Y = 3446

=>
M =3

Slope of tangent:
=>
Derivative of curve

g'(1) =3
=>
-> R is
Tangent to the curve
gas
Tangent Equation is y=34+O

d= 1
=>
=
y = 3(K) + 6 = 9 = g1f) = 9

->
ez = 1 = 32= f1911) x 92) = (s) (9) -

WT
=
x 9= 3x9 = 27

"Ay=h')=f(x).g'as +g(). f'

· hCl] = f11)g'Cl) +g(K) ·


f'1)

· "Ct) = v. (3) +
4(8)
↓ hll) = 133/3) + (3) (2) = 4 +6 = 15

y-27
=
= 15(4-1)
=>
y = 152-15 + 27


Y = 154 + 12
23]

-> cas y = cd VER


his 0 = 2n = 4 = 2

v = 1242* ==E 1825*. Co-eas

R
v I-Ra
= = &

E e

12) W

f (e) = less
[res] +

·f) =
rean+R=ECWRTS
2a4ER
:. files =

elais -
are the &
Ven2
L:
y-Y= m (21-111)

At 010,0) - m =

tblok &
roe=2a
:Y-8=24(x-d) I = 2ax

(ii) P(a,b) lies on the Tangent 1:

y
=>
= 2a (a)

b
=>
= 2 a (d)

=>b = 2,4
ec]

OS
*

(a) in
->

· #is 5
=
2.Sp+3 =
=p=2
is

2S

(b) f) = a (2-2) (2-3)

4 -

intercept: (0,0) 7-6 = a (0-2) lo-s)


-6
=> = a (6)
O
=> = -
I

(a) fle)=-1 (0-2) (03) =-I (9-3x-e4 +6)

:fly) =- 1 (80-5x+6 =- +57-6

Tangent touches curve externally at ONE point


·
.

:- 4+5x-6=kX-5

↓ O= 4+Kx-5x-5+6

eF + (K=5)
↓ +1 = 0

:
bdac=0 -> (K-55-9(1) (2) = 0

(K 5= 4 =K= 5
=> = = 12 = Kr5 =20R

K-5 =-2

K
=>
= 7 0rK=3
253

ca) cis f(x) => + (d) 2d


->
= =

(ii) 1 is the
Tangent at Al-K.K If '1 =-2K

(b) 1:y-K9=-2K(n+1)
↓ is intersecting x-axis at B (e),0)

Y

=0 0-K=-2K (x+K)

-K=-2K0-11
=>

E 2KX=-2

(c)
a=
=>
=-
Ac = 154 BC
=
2
K

T
Area
=> =
E(kY ()-Ek
↳-E,09
2s]

(as flag
-> = o-= => +3 = 24-1 1711 = 2(1)-1 = I

(b) MT = 1 = 1:y-Y2=
f(x-cle)
If y-0 (9-1)
-
=

=>
Y = -
1 (D 1)
=

=>Y =-14f 1
E
2

-> I= b = h (2) = f (g(n)]


ki )
=> = f 29(23] ·

g')
h (3)
=> = f'29(31]. g '/s)

M+Eb(s)
=> = f'(77. (4) = (-5) (4) =-20

Mt XMN=-1
=>

= o
I
Ma=
=> =
-

o
es

->
cas (i) +2)=3

(ii) +2) =
y = 5(2) +1 = 7

(b) f 108 -1)


->

gCee) =

->
gcus = f'<r+1] of(eit1) = f'lett). Less
=
f (1971), (2( 1))
-

#'(e57. (2) = 13)(2) = 6

Le:
->
P1 = 1 = 32 = 9(1) = f (1"+1) = f(2) = 7 9 M+ = 0

x-F
:
= 6(4-1) = = 0-c +7 =5 = 60 +1

Le9L intersects at G: 64+1= 34+ 1 = 3x28 SReo

Y
=> = 6 (0) +1 = 1

a
=> (0, 1)
29]

-> e=0 = f10) = 1093- 2105 + 9(0) +6 = 0 = P10,0)

->
(i) flae)= 2-24 +9() + 6

if () = 309-44+ @

(ii) Mt at $10,0) = M= = 3105-410) +a = a

Y-6= a(n-01

=> y = ax + 6
-> an +6 = 4 - 20 + a4 +G

↓O = 4-24+ax+6-ax-G

↓ -ex = 0
52 (-2) = 0

= =0 / a - 2 = 0

=x 1012 = 2
·
a is the minimum point of (n)=0

342-44 + a
=>
= 0

when x =2
= 3(2)24(2) +0 = 0

12-8
=>
+a = 0

4
=>
+a = 8

d
=> = -
4
30]

cas
cs10)=1-Sin10)=1-159=1-= i
·

· CSCO) = I
N =
1 f
obtuse ind
O is
=> = quad. I cas1)=-b
tan10)
=>
= Io
Cas COS

tanc01-
=>

fels -
(b) 0(0,0) 4m=
=-f
= tan(0)

y-0=-(x-0) IY =-e
=>

->
flal = e
"sincs-f (n)
fns
->
=

genf (since) + (sinces).


AC04] (4) -

↓ f(x) = ="cas(x) + e
"sinces-1 (1)
↓ fica) = =
"[cosces+sinces] -t
M is
->
PARALLEL to L

slopes
=>

are equal

dy or file) of a curve on at P-slope ofh


=>

e4 [cos(e) + sin(us]
-= -
=>
-

e" [C05(2)
=>
+ sin(nDzo ~

ef
=> O
1 cos() + sin(e) = o

20s() z-Sin(2)
=
*

↓ 1 = -
ten ()

:.tan()=-1=4=fanFF1) Ex
=3
31]

(a): f(x)
-> =
grtcn)
& Blies on flat and is the reflection of A in yea

:. Ba, 0)
(b) Tangent: Y-Yz= MT (21-112)
41 = 0, D1 = 0 4Mt = f') = E
In (P)

·.
yo-tp(n-a)
=tp
Y
·
l-as -
CIS

·
A 0,99 lies on
glas) =
p4 +9 = glo) = a

=>
po+9 = a

It 9
=>
= G

(I) becomes => y = (n-1-9)


~

Normal
Tangent
T
->
A

2 passes through 1-e.-e1 =-2 = ((p) (e) + 9 +1

-3
=>

=-2(np +9

= 21(p)-3=9

mem=
= isREST
(3)
InTTT

M+= = In = Incp>

p
=> = 3

From (b) -> L1 = y


=
n13s
+3
T
=> = =

y eIn
=>
=
32]

(a) fle) =-1-617+2K =-2(a-4)


-> = +'(a)
f (n-4) to

f()
=>
= - 2 (9-b). (1-0)

f)
=> =- 2 (2-1)

(b) common
tangent -> f'() =
g'c)
=-2(2-1) =
erred peres to

-2 (01-b3
=> = 24re (1-0)

-2 (0-1)
=> = 4-2
A D=3 -2 (3-4) = 23" 73-h =
-
2

h
=>
=
3+2=Ste ->
2

(c) f133 =
g/s)-13-45+2K = 23-+K

2K-K=e
=>

+3-(1) == (sey"
k +
22
=>
=
=
333

(a)
-> For A: y = 0 = 0 = In (916)
e
=>
= 4 -16

1+16
=>
= 25= 4 = INEE

e=NE7i
=> <> 0

(b) fls) In (8F-16) =+(= (2400) =


-
ess
=
·

2 E IS
F 2E-1S
:.Its = 6

=> R -62-16 = 0 EM-84+24-16=8


RC2-5)
=> + 2(2-5) = 0 5 (x-83 (2+2) = 0

x
=>
= + 8
19 - 2
347

(a)
->
+)= slope of the Tangent = G

(b) f1H) =
y = 6(4)-1 = 23

(a) R(2) = f (g(2)]

1(4)
↓ = f 29145] = + (4-3(4)) = + 116-12) = + (43

= (4) = f (9) = 23

·
a (n) = f (g(n)]

(gcns) - '(9(n) gices


1 h) +'<g1ns]. f = ·
=

.(9)
·
= f '(g (a)).g'ca)=+(4)-gm)
40s. (2 (a)-3)
-gens=e-3x
-

(0). (5-3)
= = (0)1s) =30
9) = 22-3
=>

y-23=30(x-4)
=>
D= 304 -
120+ 23

Y
=>
= 302 -97

You might also like